Analysing the Monetary and Macroprudential Policy Response Within Transmission Mechanisms of Monetary Policy on Credit Channel in Indonesia - Seprillina, Linda; Maskie, Ghozalie; Khusaini, Moh. (International Journal of Social and Local Economic Governance, 2016)
Macroeconomic policy is the one buffer to maintain economic and externally stability. However, with the integration of the world economy, it needs the right policies especialy in stablizing the financial system to balance the country’s economy. The Choice between monetary and macroprudential policy widely studied by economists, especially in the monetary policy transmission of credit channel. The macroprudential policy that is used specifically to financial stability. And the purpose of this study was to determine how the response of monetary policy the throught Bank Indonesia Certificates (SBI) and macroprudential policy is reserve requirements and loan to deposit ratio in the monetary policy transmission of credit channel in Indonesia. this research using the quantitative method that uses VECM model (vector error correction model). The results of this study is the use of monetary policy instruments with SBI can’t affect of inflation caused by variety of crucial prolems in the financial sector especially of credit sector. While macroprudential instruments showed that both instrumets have proved to be effective response an inflation rate in Indonesia.